Five-year survival of triple-negative breast cancer and the associated clinicopathological factors: a study in an Indonesian tertiary hospital - Yulian, Erwin Danil; Fachriza, Ihza (Medical Journal of Indonesia, 2023)
BACKGROUND Triple-negative breast cancer (TNBC) has a worse rate of recurrence, survival, and overall survival. This study aimed to find the survival of TNBC and its clinicopathological factors at Cipto Mangunkusumo Hospital. METHODS This study used survival analysis based on clinicopathology in 112 TNBC cases at Cipto Mangunkusumo Hospital, Jakarta, Indonesia, diagnosed from 2009 to 2019. Kaplan–Meier and log-rank tests were used for the analysis. Bivariate and multivariate analyses using Cox regression were performed to obtain the hazard ratios (HRs). RESULTS Most patients were diagnosed at the locally advanced stage (40.2%) compared to the early (33.0%) and metastatic stages (17.9%). The 5-year survival of TNBC was 81.2% with an HR value of 1.372 (p = 0.239) compared to luminal A. Bivariate analyses showed that the older age group with an HR of 6.845 (p = 0.013; CI 1.500–31.243), larger tumor size and extension (T) with an HR of 11.826 (p = 0.001; CI 2.707–51.653), broader regional lymph node involvement (N) with an HR of 8.929 (p = 0.019; CI 1.434–55.587), farther distant metastases (M) with an HR of 3.016 (p = 0.015; CI 1.242–7.322), more lymphovascular invasion with HR of 3.006 (p = 0.018; CI 1.209–7.477), and not operated-on cases with an HR of 9.165 (p<0.001; CI 3.303–25.434) significantly shortened the survival of TNBC. Multivariate analysis found that the only factor worsening the survival was not having surgery, with an HR of 6.175 (p<0.001; CI 1.518–34.288). CONCLUSIONS The 5-year survival rate of TNBC patients was 81.2%. Not having surgery was a clinicopathological factor that worsened survival outcomes in TNBC.